Implication of Mentoring and Coaching to the Self Empowerment of Economical Joint Effort Group - Sri Putri Permata (Asian Social Work Journal, 2017)
Poverty is still a prime issue in Indonesia. One of strategy which had been conducted by the government to handle poverty, by a social ministry of Republic of Indonesia is the group based empowerment for the poorest called KUBE FM (economic joint effort group). In order to endorse the development of KUBE FM, therefore, accompanied with mentoring by village mentor as well as sub- district mentor and supervision by district social services and provincial social services. The purpose of this research is to describe and analyze the implication of mentoring and coaching which had been conducted to the self-empowerment of KUBE FM. This research used a qualitative approach to a case study, located in North Bengkulu Regency of Bengkulu Province. Location of this research determined purposively which consist of 2 villages with developed KUBE FM and 2 villages with less developed KUBE FM. The result of this research indicates that there was difference on mentoring of KUBE FM. On developed KUBE FM, there was positive implication such as increasing solidarity and awareness of the importance of education, increasing business and motivation, group function run smoothly, more harmonious relationship, increasing participation and group solidity as well. On less developed KUBE FM there were not positive implication such as decreasing solidarity and awareness of the importance of education, decreasing business and motivation, group function could not run smoothly, less harmonious relationship, decreasing participation as well as group solidity. The conclusion of this research, there was the interaction between the process of mentoring and coaching to the self- empowerment of KUBE FM.